Transformasi Bidang Litbang Menjadi Badan Riset dan Inovasi Daerah Provinsi Bali - I Made Agus Gelgel Wirasuta (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
Bung Karno/Sukarno (the first president of Indonesia) placed research as the main ingredient in planning the Pola Pembangunan Semesta Berencana and used the research results on an ongoing basis to realize the ideals of national development, namely: